2005
DOI: 10.1002/cncr.21434
|View full text |Cite
|
Sign up to set email alerts
|

Results of a randomized controlled trial to increase colorectal cancer screening in a managed care health plan

Abstract: Humans have an individual profile of the electroencephalographic power spectra at the 8 to 16Hz frequency during non–rapid eye movement sleep that is stable over time and resistant to experimental perturbations. We tested the hypothesis that this electroencephalographic “fingerprint” is genetically determined, by recording 40 monozygotic and dizygotic twins during baseline and recovery sleep after prolonged wakefulness. We show a largely greater similarity within monozygotic than dizygotic pairs, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 82 publications
1
28
1
Order By: Relevance
“…This fi nding is in keeping with prior studies that have shown the superiority of patient-directed outreach over clinician-directed reminders 13 and the limited effi cacy of clinician-directed reminders on colorectal cancer screening rates. [22][23][24][25] Although the reasons for the low and in some cases lack of effi cacy of cliniciandirected reminders on colorectal cancer screening are not completely clear, the evidence overall suggests that patient-directed reminders may be a crucial component of efforts to improve colorectal cancer screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fi nding is in keeping with prior studies that have shown the superiority of patient-directed outreach over clinician-directed reminders 13 and the limited effi cacy of clinician-directed reminders on colorectal cancer screening rates. [22][23][24][25] Although the reasons for the low and in some cases lack of effi cacy of cliniciandirected reminders on colorectal cancer screening are not completely clear, the evidence overall suggests that patient-directed reminders may be a crucial component of efforts to improve colorectal cancer screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…This fi nding is in keeping with prior studies that have shown the superiority of patient-directed outreach over clinician-directed reminders 13 and the limited effi cacy of clinician-directed reminders on colorectal cancer screening rates. [22][23][24][25] Although the reasons for the low and in some cases lack of effi cacy of cliniciandirected reminders on colorectal cancer screening are not completely clear, the evidence overall suggests that patient-directed reminders may be a crucial component of efforts to improve colorectal cancer screening rates.The use of patient-directed outreach to promote colorectal cancer screening, particularly through FOBT, may also be an important strategy to address disparities in colorectal cancer screening. Although the US Preventive Services Task Force gives equal recommendation to colorectal cancer screening with FOBT, sigmoidoscopy, or colonoscopy, 2 some professional societies recommend colonoscopy as the preferred method of screening, 4 and some physicians focus heavily on colonoscopy when discussing colorectal cancer screening with patients 26 ; however, because of the ongoing fi nancial barriers to colonoscopy, particularly among the uninsured; the limited access to colonoscopy in some areas, even among the insured; and the preference of some patients for FOBT over other methods of colorectal cancer screening, 27 the use of patient-directed outreach that includes 40 Further efforts will therefore be needed to ensure appropriate endoscopic follow-up of positive FOBT tests and adequate adherence, not only to 1-time, but also to repeated FOBT screening.…”
mentioning
confidence: 99%
“…With the large number of preventive recommendations now in place, effective screening requires a "system" within the practice that facilitates the translation of recommendations into everyday care delivery; however, few practices have mechanisms in place to ensure that this happens. Indeed, evidence from quality improvement studies that focus on providing system enhancements have demonstrated efficacy for increasing CRC screening [24] while others without this focus have demonstrated either no improvement [37] or unsustainable improvements. [35] Findings from this study support the use of multidisciplinary teams and support systems as being efficacious for increasing CRC screening.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Appendix D (available online) provides a summary of measures and their properties by study. Objective measures of individual outcomes, such as completing a screening test (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)24), and measures of individual perceptions, knowledge, attitudes, or behavioral intentions (19,(25)(26)(27)(28)(29)(30)(31)(32)(33) were the most common types of measures. Of the 37 studies, almost half (43%, 16 studies) relied upon reviews of patient charts or medical records to collect key outcome data, such as screening completion.…”
Section: Measures and Measurement In Multilevel Cancer Care Interventmentioning
confidence: 99%
“…In three of the 37 studies, a measure of an individual-level phenomenon was analyzed at another level (25,32,36). For example, in the study by Ganz et al (24), individual patient screening data were aggregated to assess the organizational rate of cancer screening.…”
Section: Measures and Measurement In Multilevel Cancer Care Interventmentioning
confidence: 99%